Highly active deficient ternary sulfide photoanode for photoelectrochemical water splitting - Haimei Wang (Nature Portfolio, 2020)
While water splitting could provide a means to utilize solar energy, identifying sufficiently stable and active semiconductors is challenging. Here, authors report a deficient CdIn2S4 photoanode with improved water splitting performances due to efficient charge separation/transfer kinetics.